1996
DOI: 10.1016/s0266-7681(05)80221-9
|View full text |Cite
|
Sign up to set email alerts
|

Splint Therapy for Trigger Thumb and Finger in Children

Abstract: Forty-three trigger thumbs and fingers in 33 children (15 boys and 18 girls, average age 2 years and 4 months) were treated using a polyethylene splint. Affected digits included 40 thumbs, one index finger, and two middle fingers. The IP joint was stabilized in maximum extension via a strap on the dorsal side. The splint was applied only at night and during day-time naps. Twenty-four digits recovered completely in an average of 10 months, seven digits improved, and two digits required surgery. Eight patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
61
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 1 publication
2
61
1
4
Order By: Relevance
“…Using this approach, Nemoto et al (29) treated 43 trigger thumbs, and 24 of these cases resolved completely within 10 months after the diagnosis, seven improved and two required surgery. According to Lee et al (30) , the correction obtained through using an orthosis was more than three times greater than what was observed using observation alone (38.7 and 12.9%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, Nemoto et al (29) treated 43 trigger thumbs, and 24 of these cases resolved completely within 10 months after the diagnosis, seven improved and two required surgery. According to Lee et al (30) , the correction obtained through using an orthosis was more than three times greater than what was observed using observation alone (38.7 and 12.9%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…This statement can be correlated with the high rate of success with splinting and stretching therapy found mainly in the Southeast Asian papers. [3][4][5][6][7] One of the main concerns with conservative management is whether the child should be splinted during the observation period. Although White and Jensen 18 found it difficult to employ splinting in young children, other authors found splint, therapy, or both to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Although White and Jensen 18 found it difficult to employ splinting in young children, other authors found splint, therapy, or both to be effective. [3][4][5][6][7] In these series, the overall success rate was 78% for a mean period of treatment of 15 months. According to these authors, conservative management with splinting and stretching is an alternative to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, Skov et al later concluded that the risk of residual flexion deformity was no higher following operations conducted in patients who were more than three years old, supporting initial nonoperative treatment regardless of age 20 . Several conservative approaches to the treatment of pediatric trigger thumb with use of splints have been described by Japanese groups [10][11][12][13] , with success rates ranging from 48% to 89%. In 1998, Mulpruek and Prichasuk evaluated forty-two children to determine the rate of spontaneous recovery and treatment outcome 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Dinham and Meggitt observed that patients presenting at birth had a spontaneous recovery rate of 30% and that those presenting between six and thirty months of age had a spontaneous recovery rate of 12% 3 . Several authors have also suggested a nonoperative approach for the treatment of pediatric trigger thumb [10][11][12][13][14][15][16][17] . In the present study, patients with a diagnosis of pediatric trigger thumb were prospectively observed for at least two years, over a period ranging from twenty-four to 114 months, and the degree of flexion deformity of the interphalangeal joint was measured periodically.…”
mentioning
confidence: 99%